Liquid crystalline polymers - Wang, Xin-Jiu (World Scientific Publishing Company, 2004)
This book introduces liquid crystals and liquid crystalline polymers across six chapters. It begins with fundamental concepts and theoretical descriptions, followed by molecular engineering and phase identification techniques. The final chapters focus on the mechanical, elastic, and rheological properties of these materials. Together, they provide a comprehensive overview for both beginners and researchers.